Mantra Asihan Makrifat: Analisis Struktur, Konteks Penuturan, Proses Penciptaan, dan Fungsi - Heri Isnaini (Pusat riset dan Inovasi Nasional, 2022)
Mantras in some traditions and cultures are closely related to the values of spirituality and religiosity. Mantras can be used as a vehicle to pray and desire in the hope that they can be granted by God. Asihan becomes one type of mantra that has the function of getting the affection of the intended person. Asihan has magical powers that are suggestive that make spell pronunciation have charisma and the power to attract the attention of others. This article aims to describe the structure, context of speech, creation process, and function of the asihan. The method used in this article is descriptive-qualitative by placing text analysis as the object of research. In addition, it is also analyzed the context of mantra speech related to the practice that is a condition of obtaining the power of the mantra. The results showed that the structure of the mantra of asihan from the use of language, compounds, and themes with isotopic analysis has a relationship with the form of belief in God. Meanwhile, the context of speech and the process of creation describes the process of pronouncing mantras and practices that must be fulfilled by spell pronunciation, while the function shows the functional usefulness of mantras by spell pronunciation.